Routes to Equity Market Integration - The Interplay between Politicians, Investors and Managers - Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 2000)
Most econometric studies of equity market integration suggest that national markets are increasingly becoming part of a global equity market. As regards the extent of this integration, however, the results are often inconclusive. Further analysis calls for a closer scrutiny of the basic requirements for perfect integration. This paper presents an analysis of market segmentation in terms of existing regulatory and informational wedges, based on conditions in the Nordic welfare states. It is found that no barriers remain to cross-border equity market transactions, nor consequently to the perfect global integration of Nordic equity markets in a capital-flow perspective. However, certain residual cross-border tax wedges do challenge the view of perfect equity market integration. Further, continuing cross-border information gaps for small and medium-sized companies indicate the presence of a two-tier equity market integration.
Keywords: F30; F36; G15; G18; G38; 330; Equity market integration; Foreign equity issue; Cross-listing; Aktienmarkt; Marktintegration; Finanzmarktregulierung; Theorie